Safe Transition to Pembrolizumab following Ipilimumab-Induced Guillain-Barré Syndrome: A Case Report and Review of the Literature - Nicholas Gravbrot; Katalin Scherer; Srinath Sundararajan (Case Reports in Oncological Medicine)
Background. Immune checkpoint inhibitors are novel therapies with indications for treating several solid cancers. They are associated with immune-related adverse events, which are generally well tolerated. Though rare, severe side effects may be life-threatening. One such adverse event is Guillain-Barré syndrome, which requires cessation of the immunotherapy and intravenous immunoglobulin and/or high-dose steroids to treat. No recommendations have been published regarding restarting cancer treatment after development of immunotherapy-induced Guillain-Barré syndrome. Case Presentation. A 71-year-old gentleman with recurrent, stage IIIB melanoma was started on ipilimumab (cytotoxic T lymphocyte antigen-4 inhibitor) for adjuvant treatment following radical neck dissection and radiation therapy. After completing his third cycle of ipilimumab, he developed rapidly progressive ascending paralysis. He was diagnosed with ipilimumab-induced atypical Guillain-Barré syndrome and was treated with intravenous immunoglobulin and corticosteroids. Ipilimumab was discontinued, and the patient was monitored via surveillance imaging, as there was no evidence of active disease at that time. Several months later, he was found to have recurrent disease involving the lung, requiring right lower lobectomy. Restaging revealed thoracic lymph node involvement, and he was then started on pembrolizumab (programmed cell death protein-1 inhibitor). He experienced a complete tumoral response to pembrolizumab, and he tolerated treatment well without recurrent weakness. Conclusions. Guillain-Barré syndrome is a rare but severe complication associated with immunotherapy. Our findings suggest that in patients with a history of ipilimumab-induced Guillain-Barré syndrome, pembrolizumab may possibly be a safe and effective alternative for cancer therapy.